2015
DOI: 10.1038/jid.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

MITF Modulates Therapeutic Resistance through EGFR Signaling

Abstract: Response to targeted therapies varies significantly despite shared oncogenic mutations. Nowhere is this more apparent than in BRAF(V600E)-mutated melanomas where initial drug response can be striking and yet relapse is commonplace. Resistance to BRAF inhibitors have been attributed to the activation of various receptor tyrosine kinases (RTKs) though the underlying mechanisms have been largely uncharacterized. Here, we found that EGFR induced vemurafenib resistance is ligand dependent. We then employed whole-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 25 publications
12
82
0
Order By: Relevance
“…Second, the invasive program, and not the proliferative program, appears to be the dominant determinant of therapeutic response, since this clearly overrides the negative effect of MITF on both invasiveness and drug response. Interestingly, MITF is known to confer sensitivity to BRAFi via inhibition of EGFR expression (Ji et al 2015). We found that BMI1 expression leads to up-regulation of both EGFR and PDGFR, offering a simple mechanism to counteract the effect of MITF.…”
Section: Discussionmentioning
confidence: 88%
“…Second, the invasive program, and not the proliferative program, appears to be the dominant determinant of therapeutic response, since this clearly overrides the negative effect of MITF on both invasiveness and drug response. Interestingly, MITF is known to confer sensitivity to BRAFi via inhibition of EGFR expression (Ji et al 2015). We found that BMI1 expression leads to up-regulation of both EGFR and PDGFR, offering a simple mechanism to counteract the effect of MITF.…”
Section: Discussionmentioning
confidence: 88%
“…Recent data strongly correlated loss of MITF expression with drug resistance (46)(47)(48). miR-579-3p is an intronic miR located in intron 11 of the human gene ZFR (Zink-finger recombinase), and it is probably coexpressed with its host gene (49).…”
Section: Mir-579-3p Is Down-regulated In Melanoma Patients Who Developedmentioning
confidence: 99%
“…MITF loss at the transcriptional level occurs in four of seven melanoma cell lines, which have acquired in vitro resistance to the BRAF inhibitor PLX4720 (Muller et al., ). An independent study performed in two independent melanoma cell lines, SKMEL28 and MGH‐CH1, also showed that the emergence of vemurafenib resistance was correlated with MITF loss (Ji et al., ). Furthermore, low MITF levels and innate resistance to BRAFi have also been associated.…”
Section: Microphthalmia‐associated Transcription Factor: a Complex Rementioning
confidence: 97%
“…A second example of the impact of MITF loss on RTK activation is illustrated by the link MITF/EGFR. The emergence of vemurafenib resistance in the two melanoma cell lines, SKMEL28 and MGH‐CH1, was correlated with MITF loss, in association with EGFR activation (Ji et al., ). Further exploring this association, the investigatiors demonstrated that MITF suppression increased the expression of heparin‐binding EGF (HB‐EGF) and transforming growth factor‐α, two EGFR ligands.…”
Section: Microphthalmia‐associated Transcription Factor: a Complex Rementioning
confidence: 99%